2022
DOI: 10.1371/journal.ppat.1010641
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus uses temporospatial compartmentalization to orchestrate core versus outercapsid assembly

Abstract: Reoviridae virus family members, such as mammalian orthoreovirus (reovirus), encounter a unique challenge during replication. To hide the dsRNA from host recognition, the genome remains encapsidated in transcriptionally active proteinaceous core capsids that transcribe and release +RNA. De novo +RNAs and core proteins must repeatedly assemble into new progeny cores in order to logarithmically amplify replication. Reoviruses also produce outercapsid (OC) proteins μ1, σ3 and σ1 that assemble onto cores to create… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…6C ). Limited data on reoviruses indicated that all proteins are expressed at similar levels ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6C ). Limited data on reoviruses indicated that all proteins are expressed at similar levels ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, M is expressed at higher levels than S and ORF1a/ORF1b but shows a weaker bias against CpG ( 48 , 49 ). Finally, the little differences among ORFs observed in picornaviruses might be expected on the basis that the single ORF is translated as a polyprotein and subsequently cleaved, whereas for reoviruses limited experimental evidence suggests that all proteins are expressed at similar levels ( 42 ). Thus, it is difficult to draw definite conclusions about why individual ORFs differ in CpG content.…”
Section: Discussionmentioning
confidence: 99%
“…Another new area of research is how viral condensates interact with organelles and other cellular components to mediate viral replication and assembly functions. Some common themes emerge in the ways in which viral condensates use lipid membranes, in the form of either lipid droplets (113)(114)(115)(116) or ER membranes (117), to maximize virus production.…”
Section: Viral Condensates and Interactions With Cellular Componentsmentioning
confidence: 99%
“…Anti-reovirus polyclonal antisera were generated by immunizing rabbits with UV-inactivated mixture of purified virions of T1L and T3D. Anti-core antisera were obtained from the Maya Shmulevitz laboratory (University of Alberta) (20). mAb 8H6 and 4A3, previously described, were obtained from the Terry Dermody laboratory (University of Pittsburgh) (21).…”
Section: Reagents and Antibodies Mg132 Psi And Epoxomicin Were Purcha...mentioning
confidence: 99%